Playing non-professional football in COVID-19 time: A narrative review of recommendations, considerations, and best practices - Rico-González, M.; Pino-Ortega, J.; Ardigò, L. P. (International Journal of Environmental Research and Public Health, 2021)
The coronavirus disease (COVID-19) pandemic in 2020 resulted in widespread interruption of team sports training and competitions. Our aim was to review the recommendations and best practices in return to play in non-professional football after activity lockdown. The authors searched two electronic databases (PubMed, Web of Science) to extract studies published before September 15 2020. Twenty studies explained recommendations, considerations, or best practices in return to play in football, and all of them were clustered into three groups: (1) training load management (n = 10), (2) medical recommendations (n = 9), and (3) recovery related issues (n = 5). The way to establish a progression in training process should be based on training load management and managing the number of stimuli per time. Following the studies, this training process should be divided into three phases: phase 1—physical distancing should be maintained; phases 2 and 3—group training should start. Medical considerations were clustered into different groups: general, pre- and post- training, during training, education, planning to return to competition, and suggestions for post confinement weeks. In particular, social issues, strict hygiene questions, and continuous PCR testing should be considered in return to play over football season. Finally, since a correlation has been found between high-intensive training loads and immunoglobulin A, nutritional and lifestyle recovery strategies should be performed. Moreover, since immunosuppression has been related to congested schedules (<72 h between matches), football federations should avoid this situation.